2017
DOI: 10.1111/ajt.14215
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Events With Everolimus Exposure in Kidney Transplant Patients Receiving Low Doses of Tacrolimus

Abstract: A key objective in the use of immunosuppression after kidney transplantation is to attain the optimal balance between efficacy and safety. In a phase 3b, multicenter, randomized, open‐label, noninferiority study, the incidences of clinical events, renal dysfunction, and adverse events (AEs) were analyzed at 12 months in 309 de novo renal transplant recipients receiving everolimus (EVR), low‐dose tacrolimus (LTac), and prednisone. Cox proportional hazard regression modeling was used to estimate the probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
7
36
0
Order By: Relevance
“…In the large TRANSFORM trial, GFR was 2.3 ml/min lower in CNI/everolimus combination therapy (tacrolimus levels around 4 ng/ml) compared to CNI/MPA with tacrolimus concentrations of 6–7 ng/ml. These data together with the current study , further support the results from the pharmacodynamic analysis , suggesting aggravated nephrotoxicity even at “low” tacrolimus levels. The observation of inferior renal function after only 1–2 years of everolimus/tacrolimus combination therapy is worrisome, as nephrotoxicity usually presents many years post‐transplant, and no long‐term data on the evolution of renal function are available for everolimus/tacrolimus combination therapy.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In the large TRANSFORM trial, GFR was 2.3 ml/min lower in CNI/everolimus combination therapy (tacrolimus levels around 4 ng/ml) compared to CNI/MPA with tacrolimus concentrations of 6–7 ng/ml. These data together with the current study , further support the results from the pharmacodynamic analysis , suggesting aggravated nephrotoxicity even at “low” tacrolimus levels. The observation of inferior renal function after only 1–2 years of everolimus/tacrolimus combination therapy is worrisome, as nephrotoxicity usually presents many years post‐transplant, and no long‐term data on the evolution of renal function are available for everolimus/tacrolimus combination therapy.…”
supporting
confidence: 89%
“…Thus, in summary, this trial together with the results of other recent data provides further evidence, that MPA/tacrolimus remains current standard of care in de‐novo renal allograft recipients, despite all the well known‐limitations of this combination therapy. Everolimus is a well‐proven second‐line treatment option in case of MPA intolerability, such as severe viral infections, which are difficult to treat.…”
supporting
confidence: 55%
“…In the multicenter US 92 study, patients who received EVR and low exposure TAC showed a higher incidence of acute rejection compared to patients who received MMF and standard dose TAC. Several confounding factors may have contributed to this discrepant observation, including higher sample size, higher immunological risk, and the lower initial EVR dose used in the US study [11,12]. In fact, the lower initial EVR dose in the US trial (0.75 mg twice daily) was associated with a high proportion of patients with below-the-target EVR concentration at days 3 (62.8%), 7 (55.8%), and 14 (33.5%).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the lower initial EVR dose in the US trial (0.75 mg twice daily) was associated with a high proportion of patients with below-the-target EVR concentration at days 3 (62.8%), 7 (55.8%), and 14 (33.5%). The incidence of treated BPAR was 64.7% among patients with EVR concentrations below 3 ng/mL and 14% among those patients with EVR concentration above 3 ng/mL [12]. In our study, the initial EVR dose was 3 mg/day and only 35, 21, and 16% of patients showed concentrations below the target range at days 3, 7, and 14, with no differences between the 2 EVR groups throughout the 36 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Typical drug class associated adverse events prompted treatment discontinuation in only 11.7% of patients. Impaired renal function was the reason for treatment discontinuation in 7.4% of the patients due to suspected synergistic nephrotoxic effect, and improvements in graft function have been seen after discontinuation of the mTOR inhibitor or the calcineurin inhibitor . Yet, no significant improvement in the renal function was observed after discontinuation of EVR, suggesting that unfavorable baseline demographic characteristics, including histological abnormalities and delayed graft function, were the key risk factors accounting for this observation.…”
Section: Discussionmentioning
confidence: 99%